Coil-based Wireless Power Transfer for Implanted Pacemakers: A Brief Review - Urfa Khairatun Hisan; Liya Yusrina Sabila; Muhammad Miftahul Amri (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Nowadays, implanted permanent pacemakers (PPM) users need to undergo periodic pacemaker replacement surgery. The surgery is needed since the pacemaker's battery is usually depleted in 5-10 years. This surgery, although poses relatively low health risks, is inconvenient for PPM users. Moreover, the surgery can still be dangerous for PPM users, especially considering that most of the users are elderly. PPM replacement surgery is also costly. In addition to the costs of the surgery itself, the PPM users need to bear the price of the new PPM every time they undergo surgery. Currently, when the PPM's battery runs out, the whole PPM needs to be replaced. This is conducted to prevent the possibility of a leak in the battery seal, which might allow the body fluids to enter the PPM. Typically, once a battery is inserted into the PPM, it will be permanently sealed along with all other electronic components, and thus, battery-only replacement is impossible. Thanks to the recent advancement of wireless power transfer (WPT) technology, a PPM replacement surgery might no longer be necessary in the near future. This article presents a brief review of the current state of coil-based WPT technology and its potential applications in pacemakers. Depending on the load and transmission distance, a recent WPT system for PPM could achieve WPT efficiency as high as 97.91% on air and 78% on pig tissue medium. In terms of output power, recent works that we have summarized showed that they are able to transmit power up to 5W on a WPT system implemented on a human phantom. We also discuss the challenges, limitations, and future prospects for WPT in the medical field, particularly for PPM applications.